Effect of myofascial techniques applied to the cranial region on autonomic Nervous System analyzed by Heart Rate Variability - Cantalino, Juliana Leal Ribeiro; Salgado, Afonso Shiguemi Inoue; Santos, Israel Reis; Oliveira, Luis Vicente Franco; Oliveira, Claudia Santos; Ferreira, Luiz Alfredo Braun; Silveira, Nelson José Freitas da; Costa, Maricilia Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: To study the effect of myofascial techniques applied to the cranial region on the behavior of autonomic nervous system (ANS), using the analyses of heart rate variability. Method:This is a clinical trial study accomplished with 66 healthy subjects (33 male and 33 female). Myofascial techniques applied to the cranial area using craniosacral therapy were executed on the individuals. The Nerve-Express system, a fully automated system, was used before and after the application of the techniques to quantitatively assess the autonomic function based on heart rate variability analysis. To verify the existence of differences among the dependent variables the Wilcoxon Signed Ranks Test was used ando Mann-Whitney Test was applied in order to compare the independent variable. Results: It was observed a statistically significant increase, in the values of parasympathetic nervous system (PSNS), after the application of the technique. The quantitative values of sympathetic nervous system (SNS) decreased or did not modify in female group. This profile in female group was statistically significant although in the male group the miofascial mobilization did not modify the values of SNS. The quantitative values of SNS and PSNS behaved equal relatively in both studied groups, not being significant statistically the difference between the male and female groups. Conclusion: These results suggest that the myofascial technical appliedto the cranial area by craniossacral therapy is able to promote alterations in the behavior of ANS, generally, increasing PSNS and decreasing SNS.